Assessment of some Risk Factors of Patients with Coronary Heart Disease (CHD) in Al - Zahra Hospital in AL-Kut City (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Background: the Most public form of heart disease and the single most main cause of early death in the developed world, coronary heart disease (CHD)  extended epidemic percentage in the twentieth century. Improved knowledge about the risk factors paying to this disease could be probable to decrease the occurrence.                               Aim: To assess some risk factors of patients with (CHD) in al- Zahra hospital in the Kut city.